TRADITIONAL GAME OF WARA GHERI FOR CHILDREN’S CHARACTER BUILDING MEDIA IN ENDE - Robertus Afrianus Nanga Noo; Theodorus Sutomo Dopen Hurint (International Conference on Languages and Arts, 2014)
Game is one of the traditional media for character building. One of the traditional games in the district of Ende, Flores, NTT is Wara Gheri means 'angin literally scratching'. The community is also often called the "shell game" as a tool in the form of coconut shell game. Wara Gheri game is one of the community's cultural heritage of Ende. Participants of the game are divided into 2 groups consisting of 4 to 10 people, it could be more. This game have 5 stages: stage Sedo 'punching', stage Wegu 'kick', Sere stage Kenga or Wara Kenga 'push in the open state', Sere Kubhe stage or in a state of Were Kubhepushed face down ', and the last stage Gheri Wara.Wara Gheri game contains the value of educational, recreational, and competitive. Through this game, children are taught the importance of honesty, sportivity, unity, and solidarity. Wara Gheri game can be an alternative character education and business personalities resistance to erosion of the nation. This article is going to explore the relationship between traditional games Wara Gheri with nature-based character education children's wisdom traditions. Keywords: wisdom traditions, traditional game Wara Gheri, character education